2018
DOI: 10.1080/10717544.2018.1461276
|View full text |Cite
|
Sign up to set email alerts
|

AKT2 siRNA delivery with amphiphilic-based polymeric micelles show efficacy against cancer stem cells

Abstract: Development of RNA interference-based therapies with appropriate therapeutic window remains a challenge for advanced cancers. Because cancer stem cells (CSC) are responsible of sustaining the metastatic spread of the disease to distal organs and the progressive gain of resistance of advanced cancers, new anticancer therapies should be validated specifically for this subpopulation of cells. A new amphihilic-based gene delivery system that combines Pluronic® F127 micelles with polyplexes spontaneously formed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…AKT2, one of the three isoforms of the AKT/PKB protein kinase family, is a major effector of the canonical PI3K pathway and plays a key role in cell survival, growth, as well as apoptosis . Our previous study has also confirmed that knockdown of AKT2 suppressed cell proliferation and induced apoptosis in cervical cancer cells .…”
Section: Introductionsupporting
confidence: 57%
“…AKT2, one of the three isoforms of the AKT/PKB protein kinase family, is a major effector of the canonical PI3K pathway and plays a key role in cell survival, growth, as well as apoptosis . Our previous study has also confirmed that knockdown of AKT2 suppressed cell proliferation and induced apoptosis in cervical cancer cells .…”
Section: Introductionsupporting
confidence: 57%
“…For example, suppression of β-catenin using inhibitors for cyclin-dependent kinase 1 (CDK1; a protein kinase important for cellular transitions of G1/S and G2/M phases) is reported to overcome the resistance of CSCs to sorafenib in HCC . A point to consider is that the β-catenin pathway is indirectly reactivated after prolong application of PI3K inhibitors for patients with cancer (evidenced in HCC), so percussion is necessary for the administration of such therapies (F. Liu, Wu, Jiang, Qian, & Gao, 2018 (Rafael et al, 2018).…”
Section: Modalities To Overcome Chemo-and/or Radioresistance Of Cscsmentioning
confidence: 99%
“…Further, the importance of nanoparticles design for gene therapy is not only related with the condensation of genetic material but also with the prevention of its potential degradation. In our case, the particles obtained using the FH method present higher storage stability (64). Oncology is certainly one of the fields that is most benefiting from the application of nanotechnology to drug and gene delivery.…”
Section: Discussionmentioning
confidence: 66%
“…Unfortunately, higher sizes and polydispersity were shown, as well as lower reproducibility and stability, suffering aggregation in the presence of serum and also under storage. To overcome these technological drawbacks, we changed to the FH technique as production method (64). This method allowed the production of micelles with better physicochemical features (lower size (<30nm) and PDI, as well as neutral zeta potential).…”
Section: Discussionmentioning
confidence: 99%